2017
DOI: 10.1111/1440-1681.12868
|View full text |Cite
|
Sign up to set email alerts
|

Prorenin receptor mediates inflammation in renal ischemia

Abstract: We hypothesized that PRR contributes to renal inflammation in the 2-kidney, 1-clip (2K1C) renal ischaemia model. Male Sprague-Dawley rats were fed normal sodium diet. Blood pressure (BP) was obtained on days 0 and 28 after left renal artery clipping that reduced renal blood flow by 40%. Renal expression of TNF-α, COX-2, NF-κB, IL-1β, MCP-1 and collagen type I were assessed in sham and 2K1C rats with or without left renal administration of scramble or PRR shRNA. At baseline, there were no differences in BP. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Targeted knockdown of PRR in the clipped kidney attenuated the expression of IL-1β, TNF-α, COX-2, and NF-ҡB indicating the intricate and direct interaction between PRR and renal inflammation. 5 PRR also plays an important role in is renal dysfunction associated with diabetes. Diabetic nephropathy is characterized by increased renal inflammation and fibrosis and is strongly associated with glomerular injury leading to the development of the end-stage renal disease.…”
Section: Role Of Prr In Renal Dysfunction and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeted knockdown of PRR in the clipped kidney attenuated the expression of IL-1β, TNF-α, COX-2, and NF-ҡB indicating the intricate and direct interaction between PRR and renal inflammation. 5 PRR also plays an important role in is renal dysfunction associated with diabetes. Diabetic nephropathy is characterized by increased renal inflammation and fibrosis and is strongly associated with glomerular injury leading to the development of the end-stage renal disease.…”
Section: Role Of Prr In Renal Dysfunction and Inflammationmentioning
confidence: 99%
“…Targeted knockdown of PRR in the clipped kidney attenuated the expression of IL-1β, TNF-α, COX-2, and NF-ҡB indicating the intricate and direct interaction between PRR and renal inflammation. 5 …”
Section: Role Of Prr In Renal Dysfunction and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a similar effect of PRR on COX-2 expression has been observed in the renal medulla. 22,38 Gonzalez et al for the first time reported that COX-2 was colocalized with PRR in intercalated cells of CDs in the rat kidney. 22 In primary cultured rat renal IMCD cells, both prorenin and Ang II treatment enhanced the COX-2 and pERK1/2 expressions.…”
Section: Prr Stimulation Of Cox-2mentioning
confidence: 99%
“…22 A similar effect was observed in the 2-kidney, 1-clip (2K1C) renal ischemia rats, where PRR shRNA treatment significantly attenuated the COX-2 expression in kidney but the Ang II levels in the renal interstitial fluid were unaffected. 38 In addition, PGE 2 augments prorenin/renin protein expression in cultured M-1 CD cells, subsequently activates PRR to stimulate the COX-2 expression and further PGE 2 synthesis, 39 then increases the expression of plasminogen activator inhibitor (PAI-1) and connecting tissue growth factor (CTGF) via EP 4 receptor and TGF-β receptor-dependent Smad pathway. 16 The binding of prorenin to PRR not only induces the non-proteolytic activation of prorenin to increase its enzymatic activity, but also triggers the activation of ERK1/2 5 .…”
Section: Prr Stimulation Of Cox-2mentioning
confidence: 99%